2021
DOI: 10.1002/joc.7271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of statistical downscaling methods for climate change projections over Spain: Present conditions with perfect predictors

Abstract: The Spanish Meteorological Agency (AEMET) is responsible for the elaboration of downscaled climate projections over Spain to feed the Second National Plan of Adaptation to Climate Change (PNACC-2). The main objective of this article is to establish a comparison among five statistical downscaling methods developed at AEMET: (1) Analog, (2) Regression, (3) Artificial Neural Networks, (4) Support Vector Machines and (5) Kernel Ridge Regression. This comparison has been carried out under present conditions and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
0
17
0
2
Order By: Relevance
“…This lack of transferability has been found to be very remarkable in the cases of SVM and KRR. Experiments 1 and 2 (Hernanz et al, 2021(Hernanz et al, , 2021b showed how these two methods, which are able to reproduce complex nonlinear relationships and are based on different types of Support Vector Machines, could achieve fairly good results under present conditions, overcoming the linear method REG both with perfect and imperfect predictors, but this study has revealed some important transferability issues in them. This relates with the well-known problem of machine learning algorithms to deal with new situations to which they have not been trained, and calls in question their suitability for downscaling climate projections, as pointed out by Hsieh (2009).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This lack of transferability has been found to be very remarkable in the cases of SVM and KRR. Experiments 1 and 2 (Hernanz et al, 2021(Hernanz et al, , 2021b showed how these two methods, which are able to reproduce complex nonlinear relationships and are based on different types of Support Vector Machines, could achieve fairly good results under present conditions, overcoming the linear method REG both with perfect and imperfect predictors, but this study has revealed some important transferability issues in them. This relates with the well-known problem of machine learning algorithms to deal with new situations to which they have not been trained, and calls in question their suitability for downscaling climate projections, as pointed out by Hsieh (2009).…”
Section: Discussionmentioning
confidence: 78%
“…The five ESD methods and their different configurations (see Table 5) are briefly presented here. For a more detailed description see Hernanz et al, 2021. (a) Analog (ANA) methods (Lorenz, 1969;Zorita and von Storch, 1999) are based on the assumption of similar local conditions under similar synoptic situations, and one of their major drawbacks is their limitation to predict values outside of the observed range (Imbert and Benestad, 2005).…”
Section: Downscaling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used the projected daily temperatures (i.e., maximum and minimum) using statistical downscaling based on artificial neural networks. This has been evaluated as a suitable method to produce climate projections in the current and future scenarios in Spain while reducing the GCMs model biases ( Hernanz et al, 2022a , b ) over a grid of 5 km resolution. Two temporal horizons have been considered, namely, 2025–2045 (characterized by 2035) and 2045–2065 (characterized by 2055) to provide results for short and medium term.…”
Section: Methodsmentioning
confidence: 99%